Temperature response of a high power lithium-ion battery subjected to high current discharge. (May 2015) - Wang, C. H.; Lin, T.; Huang, J. T.; Rao, Z. H.
Abstract : Commercial LiFePO4 batteries were tested with several discharge currents (15, 20, 25, 30 and 35 A). Five k -type thermocouples were placed at the surface of each battery to evaluate the temperature distribution and electrochemical behaviour. The experiment showed that the maximum surface temperature reached 76·5°C when the current was 35 A, and the time of the maximum test temperature over 50°C was 84·42% of the total time. Supported by ANSYS software based on the implicit finite difference, the chemical reaction around the electrode, especially in anode, was more active than other places, which appeared to be higher temperature. To design a successful battery thermal management system, it is needful to study the battery temperature distribution and electrochemical behaviour. Statistical studies indicate that the maximum deviation between experimental and simulated values of the temperature distribution is ±10%.